Computer‐supported collaboration and written communication: Tools, methods, and approaches for second language learners in higher education. Issue 2 (13th October 2020) - Barrett, Neil E.; Hsu, Wei‐Chen; Liu, Gi‐Zen; Wang, Hei‐Chia; Yin, Chengjiu
Abstract: This study provides a systematic literature review of 45 selected studies into computer‐supported collaborative learning and written communication from 2006 to 2018. A review of the methodologies and findings helps explain the complex issues in this area. The corpus was analyzed qualitatively for statements, and six themes were identified: feedback, engagement, depth of discussion, language development, affective learning, and the role of the instructor. Examples include the best tools and approaches for deeper discussions and feedback, the role of the instructor, and the best practices to facilitate extended task engagement. In addition, quantitative analyses of the results revealed that most collaboration was carried out within education or English language courses, was of a duration of 11 to 20 weeks, and the most frequent sample size was between 20 and 50 students. The findings from this review contribute to our understanding of English language learning behavior, engagement with technology, and the emotional involvement in collaborative writing with technology.